Quantitative risk assessment for skin sensitisation: consideration of a simplified approach for hair dye ingredients - Goebel, Carsten; Diepgen, Thomas L. (Regulatory toxicology and pharmacology, 2012)
With the availability of the local lymph node assay, and the ability to evaluate effectively the relative skin sensitizing potency of contact allergens, a model for quantitative-risk-assessment (QRA) has been developed. This QRA process comprises: (a) determination of a no-expected-sensitisation-induction-level (NESIL), (b) incorporation of sensitization-assessment-factors (SAFs) reflecting variations between subjects, product use patterns and matrices, and (c) estimation of consumer-exposure-level (CEL). Based on these elements an acceptable-exposure-level (AEL) can be calculated by dividing the NESIL of the product by individual SAFs. Finally, the AEL is compared with the CEL to judge about risks to human health. We propose a simplified approach to risk assessment of hair dye ingredients by making use of precise experimental product exposure data. This data set provides firmly established dose/unit area concentrations under relevant consumer use conditions referred to as the measured-exposure-level (MEL). For that reason a direct comparison is possible between the NESIL with the MEL as a proof-of-concept quantification of the risk of skin sensitization. This is illustrated here by reference to two specific hair dye ingredients p-phenylenediamine and resorcinol. Comparison of these robust and toxicologically relevant values is therefore considered an improvement versus a hazard-based classification of hair dye ingredients.
Gesehen am 16.10.2018